Prediksi Omzet Penjualan Jersey menggunakan Metode Regresi Linier (Studi Kasus CV. Quattro Project Bululawang) - Raymond Gunito Farandy Junior; Nurul Hidayat; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The benefits of the jersey in the game of football are not just ordinary clothes, but as a shirt specially designed for the convenience of players. Attributes such as jersey color and back number as distinguishing information from other players. If in the game of football, the function of the jersey and attributes such as shirts, flags, colors, and jersey numbers is as a differentiator with the opponent, precisely as fans use these shirts and attributes as identity. CV. Quattro Project is one of the jersey manufacturing companies engaged in the production and procurement of sportswear. To maintain business detail and make plans for the following months then CV. Quattro Proect requires a method that can predict turnover in the next month, in this study the method used is linear regression and the data used is the turnover history data for the past year. From the tests that have been carried out almost every test, it produces the largest MAPE when used to predict turnover in November 2021, MAPE is very large because there is a significant decrease in turnover from October to November. However, overall the resulting average is good because the MAPE is only 10.23201. that means Linear Regression is a pretty good method used to do turnover predictions especially in businesses whose turnover tends to be stable.